2022
DOI: 10.1080/21645515.2022.2095837
|View full text |Cite
|
Sign up to set email alerts
|

The global mRNA vaccine patent landscape

Abstract: In light of their quick development and low risk, mRNA vaccines are gradually replacing traditional vaccines. In order to characterize the patent landscape of mRNA vaccines, this study collated mRNA vaccine–related applications that have been registered since 1962. Accordingly, the 1852 patent families were discussed in relation to their temporal distribution, geographic scope, organizational assignees, and co–patenting activities. mRNA vaccines were shown to demonstrate promise in infectious disease, cancer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…The number of patent publications relating to mRNA vaccines began to increase in about 1995 and has grown exponentially starting from about 2009 [ 25 ]. According to searches on the Derwent Innovation platform ( https://clarivate.com/products/derwent-innovation/ ), the statistics show more than 9600 related patents were registered by the end of 2021 [ 125 ]. Moreover, there are already over 15,000 patents valid and applied in major countries (such US, JP, EP, etc.)…”
Section: Current Landscape Of Mrna-based Drug Pipelinementioning
confidence: 99%
See 1 more Smart Citation
“…The number of patent publications relating to mRNA vaccines began to increase in about 1995 and has grown exponentially starting from about 2009 [ 25 ]. According to searches on the Derwent Innovation platform ( https://clarivate.com/products/derwent-innovation/ ), the statistics show more than 9600 related patents were registered by the end of 2021 [ 125 ]. Moreover, there are already over 15,000 patents valid and applied in major countries (such US, JP, EP, etc.)…”
Section: Current Landscape Of Mrna-based Drug Pipelinementioning
confidence: 99%
“…According to searches on the Derwent Innovation platform (https:// clari vate. com/ produ cts/ derwe nt-innov ation/), the statistics show more than 9600 related patents were registered by the end of 2021 [125]. Moreover, there are already over 15,000 patents valid and applied in major countries (such US, JP, EP, etc.)…”
Section: Intellectual Property Landscape For Mrna Drugsmentioning
confidence: 99%
“…The COVID‐19 pandemic's progress and its unforeseen worldwide effects have brought attention to the urgent need for safe, dependable and effective vaccines 26,27 . The messenger RNA vaccine family is one of the cutting‐edge immunization classes that has produced exceptional success against infectious disorders during the past 10 years 28,29 . This type of vaccine offers a number of significant advantages over conventional platforms, including the ability for highly quick and flexible vaccine design and production 30,31 .…”
Section: Approaches To Subunit Vaccinementioning
confidence: 99%
“…26,27 The messenger RNA vaccine family is one of the cutting-edge immunization classes that has produced exceptional success against infectious disorders during the past 10 years. 28,29 This type of vaccine offers a number of significant advantages over conventional platforms, including the ability for highly quick and flexible vaccine design and production. 30,31 Additionally, it has also been demonstrated that attenuated live vaccines are a highly effective method for preventing viral infections 32,33 Subunit vaccines have been introduced as a safer alternative to attenuated live vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with analysis showing that the US holds the most Covid-19 vaccine patents and sits at the centre of this global collaboration network. 9 Medical countermeasures provide protection (and post-exposure management) for military and civilian people against chemical, biological, radiological and nuclear material by providing rapid field-based diagnostics and therapeutics (such as antiviral medications) in addition to vaccines. 10 The race to be the next most important technological powerhouse is a close one between the UK and India, both of which claim a place in the top five countries in 29 of the 44 technologies.…”
Section: Executive Summarymentioning
confidence: 99%